PENGARUH KECERDASAN EMOSIONAL DAN POLA ASUH OTORITER TERHADAP PERILAKU BULLYING PADA SISWA SMP N 14 PURWOREJO - Satria Aldi Wicaksono; Wanodya Kusumastuti; Eko Harianto (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of emotional intelligence and authoritarian parenting on bullying behavior among students at SMP Negeri 14 Purworejo. A quantitative approach with a correlational design was employed, involving 175 students selected through stratified cluster sampling. Data were collected using validated and reliable Likert-scale questionnaires and analyzed using multiple linear regression. The results indicate that emotional intelligence and authoritarian parenting simultaneously have a significant effect on bullying behavior. However, partially, emotional intelligence shows no significant effect, while authoritarian parenting has a significant negative effect. This suggests that higher parental control and supervision are associated with lower levels of bullying behavior. The coefficient of determination of 13% indicates that the variables explain only a small portion of the variance in bullying behavior. These findings highlight that bullying is a complex phenomenon influenced by multiple factors, requiring comprehensive prevention strategies involving families, schools, and the broader social environment.